Method for testing molten iron erosion resistance of blast furnace tuyere surface protective layer

By simulating the actual working conditions of the blast furnace air outlet, building a high-temperature furnace and immersing it in simulated molten iron, combined with a variety of analytical means, the problem of deviation in the test results in the existing technology is solved, and the reliable evaluation of the anti-molecular corrosion ability of the blast furnace air outlet protective layer is achieved, supporting the research and development and optimization of materials.

CN120427501APending Publication Date: 2025-08-05TONGLING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510586464.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-08
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

The prior art is difficult to accurately simulate the complex working conditions of the blast furnace air outlet surface protective layer in actual work, resulting in a large deviation from the actual use, and it is impossible to provide a reliable basis for the research and development and performance optimization of protective layer materials.

Method used

By simulating the actual working environment of the blast furnace air outlet, a high-temperature furnace is built, simulated molten iron is configured, and the test samples are immersed in real time, the temperature and composition changes are monitored in real time, and the protection layer's anti-iron corrosion ability is evaluated and evaluation standards are set.

Benefits of technology

Tests that are closer to actual conditions are achieved, the protective layer's anti-iron corrosion resistance is accurately evaluated, reliable data support is provided, and scientific basis for the research and development and optimization of protective layer materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120427501A_ABST
    Figure CN120427501A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metallurgical material performance testing, and particularly relates to a method for testing molten iron erosion resistance of a blast-furnace tuyere surface protective layer. The test method comprises the following steps: S1, selecting a base material, preparing a protective layer on the surface of the base material, and processing a sample into a test sample piece after preparation, and S2, constructing a high-temperature smelting furnace to simulate a high-temperature environment in a blast furnace; s3, simulated molten iron is prepared, and the prepared simulated molten iron is placed in a molten iron containing container; s4, immersing the test sample piece into the simulated molten iron in the high-temperature smelting furnace, and controlling the temperature and the test time of the simulated molten iron; the temperature in the high-temperature smelting furnace and the component change of the simulated molten iron are monitored in real time; s5, ending the test, taking out the test sample, observing the microstructure change of the protective layer on the surface of the test sample, and analyzing the element composition and content change; the erosion rate of the protective layer is calculated by measuring the mass loss and the size change of the test sample; and S6, comprehensively evaluating the molten iron erosion resistance of the protective layer according to various data.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgical material performance testing, and particularly relates to a method for testing the ability of a protective layer on a blast furnace tuyere surface to resist molten iron corrosion. Background Art

[0002] The blast furnace tuyere is a key component in the blast furnace ironmaking process. Its working environment is extremely harsh, and it is subjected to high temperature, high-speed airflow erosion and molten iron erosion for a long time. In order to increase the service life of the blast furnace tuyere, a protective layer is usually coated or prepared on its surface. The quality of the protective layer's resistance to molten iron erosion directly affects the service life of the blast furnace tuyere and the stable operation of the blast furnace. However, the current test method for the resistance of the protective layer on the surface of the blast furnace tuyere to molten iron erosion is still imperfect. Existing test methods are often difficult to accurately simulate the complex working conditions of the blast furnace tuyere in actual work, resulting in a large deviation between the test results and the actual usage, and cannot provide a reliable basis for the research and development and performance optimization of the protective layer material. Therefore, there is an urgent need to develop a method that can truly simulate the working environment of the blast furnace tuyere and accurately test the ability of the protective layer to resist molten iron erosion. Summary of the Invention

[0003] In response to the shortcomings of the existing technology, the present invention proposes a method for testing the ability of the protective layer on the surface of the blast furnace tuyere to resist molten iron erosion. By simulating the actual working environment of the blast furnace tuyere, the anti-molten iron erosion performance of the protective layer can be accurately evaluated, providing a scientific basis for the research and development and application of blast furnace tuyere protective layer materials.

[0004] A method for testing the ability of a blast furnace tuyere surface protective layer to resist molten iron corrosion, the testing method comprising the following steps:

[0005] S1. Select a base material that is the same or similar to the actual blast furnace tuyere material, and prepare a protective layer on the surface of the base material that is the same as the actual use process. After the preparation is completed, process the sample into a test sample with the same size and specifications.

[0006] S2. Build a high-temperature furnace to simulate the high-temperature environment inside a blast furnace;

[0007] S3. Prepare simulated molten iron according to the chemical composition of the actual blast furnace molten iron, and place the prepared simulated molten iron in a molten iron container;

[0008] S4. Fix the test sample on a high-temperature resistant fixture and slowly immerse the test sample in simulated molten iron in a high-temperature furnace through the fixture. Control the temperature of the simulated molten iron and set the test time. During the test, monitor the temperature in the high-temperature furnace and the composition changes of the simulated molten iron in real time.

[0009] S5. After the test, remove the test sample and cool it to room temperature; observe the micromorphology of the protective layer on the surface of the test sample, and analyze the changes in the element composition and content of the protective layer; calculate the erosion rate of the protective layer by measuring the mass loss and dimensional change of the test sample. The specific calculation formula is: erosion rate = (mass of the sample before the test - mass of the sample after the test) / (test time × surface area of the sample immersed in the molten iron);

[0010] S6. Comprehensively evaluate the ability of the protective layer to resist molten iron corrosion based on the microscopic morphology, elemental composition, mass loss, dimensional change, and erosion rate data of the surface protective layer of the test sample.

[0011] Furthermore, in step S1, the shape of the test sample is set to be cylindrical, with a diameter of (20-30) mm and a height of (25-35) mm.

[0012] Furthermore, in step S2, the high temperature environment temperature inside the simulated blast furnace is (1400-1700)°C, and the temperature fluctuation range is controlled within ±(5-30)°C; a molten iron container is also required to be set inside the high temperature furnace.

[0013] Furthermore, the main components and contents of the simulated molten iron in step S3 are: iron (94-95)%, carbon (3-4)%, silicon (1.0-1.5)%, manganese (0.5-1)%, phosphorus (0.15-0.20)%, and sulfur (0.05-0.10)%.

[0014] Furthermore, in step S4, the depth of the test sample immersed in the molten iron is maintained at (20-30) mm. The temperature of the simulated molten iron is controlled to be maintained at (1450-1600)°C, and the test time is set to (5-10) hours.

[0015] Furthermore, in step S5, the microscopic morphology of the protective layer on the surface of the test sample is observed using an optical microscope or a scanning electron microscope.

[0016] Furthermore, in step S5, the element composition and content changes of the protective layer surface of the test sample are analyzed using an energy spectrometer.

[0017] Furthermore, the evaluation criteria in step S6 are: when the erosion rate is less than 0.1 g / (h·cm 2 ), it is judged that the protective layer has excellent resistance to molten iron corrosion; when the corrosion rate is 0.1-0.2g / (h·cm 2 ), the protective layer is judged to have good resistance to molten iron corrosion; when the corrosion rate is greater than 0.2g / (h·cm 2 ), it is determined that the protective layer has poor resistance to molten iron corrosion.

[0018] Beneficial effects of the present invention:

[0019] 1. The present invention simulates the high temperature, molten iron erosion and other working conditions of the blast furnace tuyere in actual operation, making the test environment closer to the actual situation, and can accurately evaluate the anti-molten iron erosion ability of the blast furnace tuyere surface protective layer, and the test results are highly reliable;

[0020] 2. Using a variety of analytical methods, the protective layer is analyzed from multiple perspectives such as micromorphology, elemental composition, quality and dimensional changes, and the performance of the protective layer is comprehensively and systematically evaluated, providing detailed data support for the research and development and optimization of the protective layer material;

[0021] 3. Clear result evaluation standards are set to facilitate intuitive judgment of the quality of the protective layer's ability to resist molten iron corrosion, providing a scientific basis for the selection of protective layer materials in actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present disclosure or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0023] Figure 1 Detailed flow chart of the test method of the present invention. DETAILED DESCRIPTION

[0024] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0025] A method for testing the ability of a blast furnace tuyere surface protective layer to resist molten iron corrosion comprises the following steps:

[0026] Sample preparation: Select a base material that is the same or similar to the actual blast furnace tuyere material, and prepare a protective layer on the surface of the base material using the same process as in actual use. After preparation, process the sample into a test specimen with consistent dimensions. The test specimen is cylindrical in shape with a diameter of (20-30) mm and a height of (25-35) mm.

[0027] Simulation environment setup: Build a high-temperature furnace to simulate the high-temperature environment inside a blast furnace. The high-temperature furnace can heat up to (1400-1700)°C, and the temperature fluctuation range is controlled within ±(5-30)°C. Set up a molten iron container inside the high-temperature furnace. The molten iron container is made of high-temperature and corrosion-resistant materials. Its shape and size must be able to accommodate a sufficient amount of molten iron and ensure that the test specimens can be completely immersed in the molten iron.

[0028] Molten iron preparation: Prepare simulated molten iron according to the chemical composition of actual blast furnace molten iron. The main components and contents of the simulated molten iron are: iron (94-95)%, carbon (3-4)%, silicon (1.0-1.5)%, manganese (0.5-1)%, phosphorus (0.15-0.20)%, and sulfur (0.05-0.10). Place the prepared simulated molten iron in a molten iron container.

[0029] Test process: Fix the test sample on a high-temperature resistant fixture and slowly immerse the test sample into the simulated molten iron in the high-temperature furnace through the fixture, so that the depth of the test sample in the molten iron is maintained at (20-30) mm. The temperature of the simulated molten iron is controlled to be maintained at (1450-1600) ° C, and the test time is set to (5-10) hours. During the test, the temperature in the high-temperature furnace and the changes in the composition of the simulated molten iron are monitored in real time;

[0030] Sample analysis: After the test, the test sample was removed and cooled to room temperature. Optical microscope, scanning electron microscope (SEM) and other equipment were used to observe the microscopic morphology changes of the protective layer on the surface of the test sample, and energy dispersive spectrometer (EDS) was used to analyze the elemental composition and content changes of the protective layer. At the same time, the erosion rate of the protective layer was calculated by measuring the mass loss and dimensional change of the test sample. The specific calculation formula is: Erosion rate = (mass of the sample before the test - mass of the sample after the test) / (test time × surface area of the sample immersed in molten iron);

[0031] Result evaluation: Based on the micromorphology, element composition, mass loss, dimensional change and erosion rate of the surface protective layer of the test sample, the ability of the protective layer to resist molten iron erosion is comprehensively evaluated. Different evaluation level standards are set; the specific evaluation standard is: when the erosion rate is less than 0.1g / (h·cm 2 ), it is judged that the protective layer has excellent resistance to molten iron corrosion; when the corrosion rate is 0.1-0.2g / (h·cm 2 ), the protective layer is judged to have good resistance to molten iron corrosion; when the corrosion rate is greater than 0.2g / (h·cm 2 ), it is determined that the protective layer has poor resistance to molten iron corrosion.

[0032] The test method is further verified by two specific examples below.

[0033] Example 1

[0034] Sample preparation: Q235 steel was selected as the base material, and a ceramic protective layer was prepared on the surface of the base material using a thermal spraying process. The prepared sample was processed into a cylindrical test specimen with a diameter of 20 mm and a height of 30 mm.

[0035] Simulation environment setup: A high-temperature resistance furnace was built to simulate the high-temperature environment inside a blast furnace. The furnace was capable of heating to 1500°C, with a temperature fluctuation range controlled within ±5°C. A graphite crucible was placed inside the furnace to hold the molten iron.

[0036] Molten iron preparation: According to the chemical composition of actual blast furnace molten iron, simulated molten iron is prepared. Its main components and contents are: 94% iron, 3.8% carbon, 1.2% silicon, 0.8% manganese, 0.15% phosphorus, and 0.05% sulfur. The prepared simulated molten iron is placed in a graphite crucible;

[0037] Test procedure: The test specimen is fixed to a molybdenum fixture and slowly immersed in simulated molten iron in a high-temperature resistance furnace. The fixture maintains the specimen's immersion depth at 20 mm. The simulated molten iron temperature is maintained at 1450°C, and the test duration is set to 5 hours. During the test, a thermocouple is used to monitor the temperature in the high-temperature resistance furnace in real time, and small amounts of simulated molten iron are periodically sampled for composition analysis.

[0038] Sample analysis: After the test, the test sample was taken out and cooled naturally to room temperature. An optical microscope was used to observe the macroscopic morphology of the protective layer on the surface of the test sample, and some small cracks and holes were found on the surface of the protective layer. A scanning electron microscope (SEM) was used to observe the micromorphology of the protective layer to further clarify the distribution and size of the cracks and holes. The elemental composition of the surface of the protective layer was analyzed by an energy dispersive spectrometer (EDS), and it was found that the iron content increased and some elements in the ceramic protective layer were lost. At the same time, a high-precision balance was used to measure the mass loss of the test sample, and a caliper was used to measure the dimensional change of the sample. The erosion rate of the protective layer was calculated to be 0.05g / (h·cm 2 );

[0039] Result evaluation: According to the set evaluation standard, the erosion rate is 0.05g / (h·cm 2 ) is less than 0.1g / (h·cm 2 ), it is determined that the protective layer has excellent resistance to molten iron corrosion.

[0040] Example 2

[0041] Sample preparation: 316L stainless steel was selected as the base material. A metal alloy protective layer was prepared on the surface of the base material using a chemical vapor deposition (CVD) process. The sample was processed into a cylindrical test specimen with a diameter of 20 mm and a height of 30 mm.

[0042] Simulation environment construction: Build a high-temperature resistance furnace to simulate the high-temperature environment inside a blast furnace. The high-temperature resistance furnace can heat up to 1600°C, and the temperature fluctuation range is controlled within ±10°C. Build a high-temperature resistance furnace to simulate the high-temperature environment inside a blast furnace, and use a graphite crucible as a container for molten iron;

[0043] Molten iron preparation: According to the chemical composition of actual blast furnace molten iron, simulated molten iron is prepared. Its main components and contents are: iron 94.3%, carbon 3.3%, silicon 1.4%, manganese 0.8%, phosphorus 0.15%, sulfur 0.05%. The prepared simulated molten iron is placed in a graphite crucible;

[0044] Test procedure: The test specimen is fixed to a molybdenum fixture and slowly immersed in simulated molten iron in a high-temperature resistance furnace. The fixture maintains the specimen's immersion depth at 25mm. The simulated molten iron temperature is maintained at 1500°C, and the test duration is set to 3 hours. During the test, a thermocouple is used to monitor the temperature in the high-temperature resistance furnace in real time, and small amounts of simulated molten iron are periodically sampled for composition analysis.

[0045] Sample analysis: After the test, the test samples were analyzed. Optical microscopy revealed obvious signs of erosion on the protective layer surface, and SEM observation revealed a large area of peeling on the protective layer surface. EDS analysis showed a significant increase in the iron content of the protective layer surface and a decrease in the alloying element content. The measured and calculated erosion rate of the protective layer was 0.12 g / (h·cm 2 );

[0046] Result evaluation: According to the evaluation standard, the erosion rate is 0.12g / (h·cm 2 ) in the range of 0.1-0.2g / (h·cm 2 ), it is determined that the protective layer has good resistance to molten iron corrosion.

[0047] Result analysis:

[0048] 1. The present invention simulates the high temperature, molten iron erosion and other working conditions of the blast furnace tuyere in actual operation, making the test environment closer to the actual situation, and can accurately evaluate the anti-molten iron erosion ability of the blast furnace tuyere surface protective layer, and the test results are highly reliable;

[0049] 2. Using a variety of analytical methods, the protective layer is analyzed from multiple angles such as micromorphology, elemental composition, quality and dimensional changes, and the performance of the protective layer is comprehensively and systematically evaluated, providing detailed data support for the research and development and optimization of the protective layer materials.

[0050] Throughout this specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.

[0051] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention, and such changes and modifications fall within the scope of the invention as claimed.

Claims

1. A method for testing the ability of a blast furnace tuyere surface protective layer to resist molten iron corrosion, characterized in that: The test method comprises the following steps: S1. Select a base material that is the same or similar to the actual blast furnace tuyere material, and prepare a protective layer on the surface of the base material using the same process as in actual use. After preparation, process the sample into test specimens with consistent dimensions and specifications; S2. Build a high-temperature furnace to simulate the high-temperature environment inside a blast furnace; S3. Prepare simulated molten iron according to the chemical composition of the actual blast furnace molten iron, and place the prepared simulated molten iron in a molten iron container; S4. Fix the test sample on a high-temperature resistant fixture and slowly immerse the test sample in simulated molten iron in a high-temperature furnace through the fixture. Control the temperature of the simulated molten iron and set the test time. During the test, monitor the temperature in the high-temperature furnace and the composition changes of the simulated molten iron in real time. S5. After the test, remove the test sample and cool it to room temperature; observe the micromorphology of the protective layer on the surface of the test sample, and analyze the changes in the element composition and content of the protective layer; calculate the erosion rate of the protective layer by measuring the mass loss and dimensional change of the test sample. The specific calculation formula is: erosion rate = (mass of the sample before the test - mass of the sample after the test) / (test time × surface area of the sample immersed in the molten iron); S6. Comprehensively evaluate the ability of the protective layer to resist molten iron corrosion based on the microstructure, elemental composition, mass loss, dimensional change, and erosion rate data of the surface protective layer of the test sample.

2. The method for testing the anti-molten iron corrosion ability of the blast furnace tuyere surface protective layer according to claim 1, characterized in that: In step S1 , the shape of the test sample is set to be cylindrical, with a diameter of (20-30) mm and a height of (25-35) mm.

3. The method for testing the anti-molten iron corrosion ability of the blast furnace tuyere surface protective layer according to claim 2, characterized in that: In step S2, the high temperature environment temperature inside the simulated blast furnace is (1400-1700)°C, and the temperature fluctuation range is controlled within ±(5-30)°C; a molten iron container is also required to be set inside the high temperature furnace.

4. The method for testing the ability of a blast furnace tuyere surface protective layer to resist molten iron corrosion according to claim 1, characterized in that: The main components and contents of the simulated molten iron in step S3 are: iron (94-95)%, carbon (3-4)%, silicon (1.0-1.5)%, manganese (0.5-1)%, phosphorus (0.15-0.20)%, and sulfur (0.05-0.10)%.

5. The method for testing the anti-molten iron corrosion capability of the blast furnace tuyere surface protective layer according to claim 1, characterized in that: In step S4, the depth of the test sample immersed in the molten iron is maintained at (20-30) mm. The temperature of the simulated molten iron is controlled to be maintained at (1450-1600)°C, and the test time is set to (5-10) hours.

6. The method for testing the ability of a blast furnace tuyere surface protective layer to resist molten iron corrosion according to claim 1, characterized in that: In step S5, the microscopic morphology of the protective layer on the surface of the test sample is observed using an optical microscope or a scanning electron microscope.

7. The method for testing the ability of a blast furnace tuyere surface protective layer to resist molten iron corrosion according to claim 1, characterized in that: In step S5, the element composition and content changes of the protective layer surface of the test sample are analyzed using an energy spectrometer.

8. The method for testing the ability of a blast furnace tuyere surface protective layer to resist molten iron corrosion according to claim 1, characterized in that: The evaluation criteria in step S6 are: when the erosion rate is less than 0.1 g / (h·cm 2 ), it is judged that the protective layer has excellent resistance to molten iron corrosion; when the corrosion rate is 0.1-0.2g / (h·cm 2 ), the protective layer is judged to have good resistance to molten iron corrosion; when the corrosion rate is greater than 0.2g / (h·cm 2 ), it is determined that the protective layer has poor resistance to molten iron corrosion.